Development of an empirical relationship to predict the joint tensile strength and joint shear strength of diffusion bonded AA6082 aluminium alloy. (3rd May 2019) - Venugopal, S.; Mahendran, G.
In this work, empirical relationships were developed to predict the joint tensile strength and joint shear strength of the rolled plates made of 5 mm thick aluminium alloy AA6082, joined by diffusion bonding. Three diffusion bonding parameters such as bonding temperature, bonding pressure and holding time were used to formulate the relationship. A central composite design was also put to use to minimise the number of experimental conditions. In addition, the response surface methodology was employed to develop the relationship. The relationship thus developed can effectively predict, to the 95% confidence level, the strength of diffusion bonded AA6082 aluminium alloys. It was observed that the joint tensile strength and joint shear strength went up with the increase in either bonding temperature or bonding pressure. The maximum joint tensile strength and joint shear strength were observed as 36 MPa and 115 MPa at 520°C and 10 MPa pressure. It was evidently due to the diffusion of atoms in the interface. Metallurgical characterisation was performed using optical microscopy and SEM.